2019
DOI: 10.1520/ssms20190001
|View full text |Cite
|
Sign up to set email alerts
|

A Wood Recovery Assessment Method Comparison between Batch and Cellular Production Systems in the Furniture Industry

Abstract: Enhanced wood recovery mirrors a successful wood manufacturing operation. Studies of wood recovery in secondary wood processing, however, are scarce, particularly in furniture manufacturing. Although recovery rates are under the continuous surveillance of sophisticated technology, this attempt to monitor wood recovery would be especially challenging for small-to medium-sized furniture enterprises, as the capital investment in such technology would be substantial. This would hinder the possibility for improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…Moreover, the layout influences the production capacity, being considered one of the factors related to higher costs and lower wood recovery rates. The total wood recovery rate was of 29.6% in one industry and of 23.7% in another [57]. The same study showed that methods to assess the physical layout and the production systems are important to allow the identification of critical points and opportunities to recover materials for reuse.…”
Section: (Re)layout Projects As a Strategy To Implement Cp In The Fur...mentioning
confidence: 87%
“…Moreover, the layout influences the production capacity, being considered one of the factors related to higher costs and lower wood recovery rates. The total wood recovery rate was of 29.6% in one industry and of 23.7% in another [57]. The same study showed that methods to assess the physical layout and the production systems are important to allow the identification of critical points and opportunities to recover materials for reuse.…”
Section: (Re)layout Projects As a Strategy To Implement Cp In The Fur...mentioning
confidence: 87%